A Chemosystematic study of the flavonoids of Vigna - Lattanzio, V.; Cardinali, A.; Linsalata, V.; Perrino, P.; Ng, N.Q. (Springer, 1996)
Flavonoid chemical markers together with other biochemical markers and/or morphological data can provide useful characters for defining species in Vigna genus. In this paper flavonoid HPLC fingerprints have been utilized to assess taxonomic relationships amongst species and accessions of Vigna.Within the taxa analysed there is evidence of both infra- and interspecific chemical variations. In some species chromatographic data support evidence for the existence of different flavonoid chemotypes, which may reflect differences in geographic origin. As far as interspecific relationships are concerned, species belonging to sections Vigna, Plectotropis and Ceratotropis do not show flavonoid glycosides in common with cultivated lines of Vigna. By contrast, some relationships have been found between cultivated lines and wild species of section Catiang. Kaempferol-3-rutinoside and an unidentified kaempferol-glycoside were the only flavonoids detected in the three subgenera analysed. Finally, a greater variability in flavonoid aglycone class and glycosylation pattern has been observed in cultivars of V. unguiculata (L.) Walp. compared to the wild species. This observation may confirm that cultivation and/or domestication may cause or increase species diversification.